Development of learning media lathe machining based on animation video - Wahyu Mustafa Kusuma; Setuju Setuju; Dianna Ratnawati (Universitas Sarjanawiyata Tamansiswa, 2019)
The objectives of this study are to develop a job sheet for the practice of animation video-based lathe machining for the learning media and test the level of feasibility of the results produced. This research method is Research and Development (R&D) with a 4-D model consisting of four stages, namely define, design, develop, and disseminate. The subject of the study consisted of material experts, media experts, and students of class XI machining techniques at Muhammadiyah Vocational School Prambanan. The object of the study is the flat lathe machining technique of class XI machining techniques. The instrument used was a questionnaire. While the data analysis technique uses quantitative descriptive analysis. The applications used in developing this job sheet include SSCNC (Swansoft CNC Simulator), bandicam, and wondershare filmora. The results of this study include: (1) the research produced an animation video-based learning media consisting of 6 subjects; and (2) the level of feasibility of animated videos is very feasible, it is known from the results of material expert validation reaching an average value of 71.50 with a percentage of 89.50% in the very feasible category. The results of media expert validation reached a value of 73 with a percentage of 91% in the very feasible category. The results of the small class test obtained an average score of 62.31 with a percentage of 86% in the very feasible category and the results of the large class test obtained an average score of 59.55 with a percentage of 83% in the very feasible category.